1958
DOI: 10.1038/181290a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Triploidy in the South African Clawed Frog, Xenopus laevis (Daudin)

Abstract: The rate of increase in the area shown on the graph, representing fissipede evolution, changes in the Vindobonian, and the values obtained when represented as co-ordinates plotted against •t.ime provide a graphic expression of this phenomenon (Fig. 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1959
1959
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Multiploid cells have been shown to suffer from chromosomal instability and degenerate. However, triploid individuals that result from transplantation of two male nuclei are stable and develop to adulthood (Smith, 1958; Kawahara, 1978; Tompkins, 1978; Tompkins and Reinschmidt, 1991; Noramly et al, 2005). It is not known if these animals are fertile (?)…”
Section: Two Decades Of Transgenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Multiploid cells have been shown to suffer from chromosomal instability and degenerate. However, triploid individuals that result from transplantation of two male nuclei are stable and develop to adulthood (Smith, 1958; Kawahara, 1978; Tompkins, 1978; Tompkins and Reinschmidt, 1991; Noramly et al, 2005). It is not known if these animals are fertile (?)…”
Section: Two Decades Of Transgenesismentioning
confidence: 99%
“…This usually leads to the formation of bigger cells and can be directly quantified by FACS analyses (Flajnik et al, 1984). Alternatively, counting the proportion of nucleoli in cells will give a good estimation of the ploidy status of the individuals, as deviation from the expected frequencies is indicative of chromosome number mosaics (Smith, 1958; Muller et al, 1978). A simple karyotype will provide a lot of information, but the use of FISH (fluorescent in situ hybridization) analyses on chromosomes from transgenic individuals would be greatly beneficial.…”
Section: Specific Features Of Transgenic Animals Generated By the Remmentioning
confidence: 99%
“…Under laboratory breeding conditions, it is not rare to find triploid Xenopus among the offspring. They arise most probably through retention of the second polar body in the egg, since the second meiotic division after fertilization is easily disturbed by temperature shock (SMITH, 1958;KAWAHARA, 1978), pressure (MuLLER et al, 1978;ToMPKINS, 1978) or by mechanical deformation of eggs. Polyspermy and mis-divisions in early embryonic development are other occasions which result in autopolyploid individuals.…”
Section: Mechanisms Of Polyploidizationmentioning
confidence: 99%
“…Triploids and tetraploids have also been obtained in Xenopus. Smith (1958) found that a 5 min. heat shock (36.1-36-5" C.) within 10 min.…”
Section: ( D ) Sources Of the Yolk Protein Of The Oocytementioning
confidence: 99%